Case Report: Cerebral folate deficiency caused by FOLR1 variant - Wang, Qian; Yang, Jie; Yu, Chunmei; Deng, Yao; Wen, Qianhui; Yang, Hua; Liu, Hao; Luo, Rong (Frontiers in Pediatrics, 2024)
Background: Cerebral folate transport deficiency (CFD) is a rare neurological disease characterized by a deficiency in 5-methyltetrahydrofolate (5-MTHF) in the cerebrospinal fluid, with a normal peripheral total folate level. Late infantile-onset refractory seizures, ataxia, movement disorders, hypotonia, developmental delays, and developmental regression characterize CFD. Some patients present with visual and hearing impairments and autism-like manifestations. This study aimed to elucidate the clinical features, diagnostic approach, and therapeutic outcomes in siblings with CFD due to FOLR1 variants, highlighting the importance of early diagnosis and treatment. Case presentation: We reported the cases of two siblings with CFD caused by a new variant in FOLR1. They presented with intractable epilepsy, developmental regression, and ataxia, and the younger sibling developed autism. Whole-exon sequencing revealed a c.148G>A homozygous variant, resulting in a change in the amino acid sequence (p.Glu50Lys). Low 5-MTHF levels were detected in the cerebrospinal fluid. Conclusions: This report illustrates that CFD was caused by FOLR1 variants in two siblings. They had intractable epilepsy, developmental regression, and ataxia, and a diagnosis of CFD was confirmed by a c.148G>A (p.Glu50Lys) variant in FOLR1, a new pathogenic variant in FOLR1. Early diagnosis is essential and can improve outcomes in affected patients. 1 Background Cerebral folate transport deficiency (CFD) is a rare autosomal recessive genetic disease caused by a deficiency of 5-methyltetrahydrofolate (5-MTHF) in the cerebrospinal fluid (CSF), leading to various